(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Whether different affective states have specific physiological activation patterns still does not have an exact interpretation and clear validation. Skin Conductance Response (SCR) is under strict control of the autonomic nervous system, providing an efficient way to measure the emotional reactions. Since the emotional SCR signals are always short and noisy, it is of great value to study the methods suitable for short-term SCR analysis. According to the characteristic of SCR signal, we proposed a symbolic method and the symbolic information entropy, further, applied the method to analyse emotional SCR signals. Experiment results show that the symbolic information entropy of SCR is in accordance with the arousal level of emotions, and SCR is more sensitive to the variations of emotional arousal rather than to valence. Symbolic information entropy is less influenced by noise and non-stationary, providing an effective method in analyzing SCR signals or other complex physiological signals.